2018
DOI: 10.1155/2018/3093516
|View full text |Cite
|
Sign up to set email alerts
|

Huanglian-Wendan Decoction Inhibits NF-κB/NLRP3 Inflammasome Activation in Liver and Brain of Rats Exposed to Chronic Unpredictable Mild Stress

Abstract: Depression is a common mental disorder in modern society. A traditional Chinese medicine Huanglian-Wendan decoction with potential anti-inflammation is used as a clinical antidepressant. Our previous study showed central and peripheral inflammatory responses in a rat model of depression developed by chronic unpredictable mild stress (CUMS). Here, we investigated the anti-inflammatory activity and mechanism of Huanglian-Wendan decoction in CUMS rats. LC-MS/MS and HPLC were performed to determine the major compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 37 publications
3
14
0
Order By: Relevance
“…Depression has been on the rise in recent years as a result of increases in stress in everyday life. Increasing evidence has indicated that the excessive secretion of proinflammatory cytokines, including MCP-1, IL-1β, IL-6, and TNF-α, results in behavior similar to that of depression [ 28 ]. Here, we also found that MCP-1, IL-1β, IL-6, and TNF-α expression was increased after the induction of depression in both in vivo and in vitro experiments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depression has been on the rise in recent years as a result of increases in stress in everyday life. Increasing evidence has indicated that the excessive secretion of proinflammatory cytokines, including MCP-1, IL-1β, IL-6, and TNF-α, results in behavior similar to that of depression [ 28 ]. Here, we also found that MCP-1, IL-1β, IL-6, and TNF-α expression was increased after the induction of depression in both in vivo and in vitro experiments.…”
Section: Discussionmentioning
confidence: 99%
“…The tissues were cut coronally into 4-μm slices with a sliding vibratome (CM1900; Leica Microsystems, Wetzlar, Germany). The immunofluorescence and statistical methods were based on previously described methods [ 28 ]. Brains sections that contained the hippocampus were permeabilized with 0.5% Triton X-100 for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…Several in vitro and in vivo studies suggested that Andro was able to activate the Wnt/β-Catenin signalling pathway, inducing the transcription of Wnt target genes and inhibiting glycogen synthase kinase3β (GSK3β) by dephosphorylation (Jiang et al, 2015; Tapia-Rojas et al, 2015; Varela-Nallar et al, 2015). Many studies have implicated the role of β-Catenin, GSK3β, NF-κB, and the NLRP3 inflammasome in the pathogenesis of depression, as (1) chronic stress significantly reduced the total and nuclear levels of β-Catenin in the hippocampus of rats (Hui et al, 2018); (2) GSK3β was highly expressed and phosphorylated in the brain of chronically stressed mice, while inhibition of GSK3β led to antidepressant-like actions (Peng et al, 2018); and (3) several antidepressants exerted antidepressant-like effects in mice via the inhibition of NF-κB and the NLRP3 inflammasome (Jia et al, 2018; Song et al, 2018a, 2018b). Therefore, it is possible that these molecules also contribute to the antidepressant-like actions of Andro in mice, and more antagonists/shRNAs will be used in our further study.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, confocal microscopy analysis intuitively demonstrated the inhibitory effect of HZTF on ASC dimerization. These results suggested that HZTF may prevent gout by inhibiting NALP3 inflammasome as well as blocking the NF- κ b signaling pathway, which will increase the expression of IL-1 β , IL-6, and TNF- α [49].…”
Section: Discussionmentioning
confidence: 99%